PEMANFAATAN HAK KEKAYAAN INTELEKTUAL SEBAGAI JAMINAN KREDIT MENURUT PERATURAN PEMERINTAH TENTANG EKONOMI KREATIF - Roberth Nico Sinaga; Candra Irawan; Widiya N. Rosari (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Law Number 24 of 2019 concerning the Creative Economy is further regulated and specifically Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy. The aim of this research is to analyze the use of Intellectual Property as credit collateral in the form of fiduciary guarantees and to determine the economic value of an Intellectual Property Certificate which is used as financing collateral. This research is normative legal research, namely doctrinal legal research with a statutory approach, conceptual approach, comparative law approach. This research uses primary data and secondary data obtained through document study and interviews. The data is processed by analyzing techniques using qualitative methods. The results of this research show that some IPRs have different time periods and are limited in obtaining ownership. Intellectual Property in other forms can be the object of debt collateral such as Articles and Explanations 7, 8 and 9 of Government Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy. This research determines that Intellectual Property that can be used as the subject of debt collateral must meet two requirements based on the description in the discussion of Article 10 of Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy. First, the intellectual property must be and has been registered or registered with the Directorate General of Intellectual Property (DJKI) of the Ministry of Law and Human Rights. Second, goods with intellectual property that are managed independently or licensed to other parties based on agreements.